Effect : an introduction to research design and causality - Huntington-Klein, Nick. (Boca Raton: CRC Press, 2022)
"The Effect: An Introduction to Research Design and Causality is about research design, specifically concerning research that uses observational data to make a causal inference. It is separated into two halves, each with different approaches to that subject. The first half goes through the concepts of causality, with very little in the way of estimation. It introduces the concept of identification thoroughly and clearly and discusses it as a process of trying to isolate variation that has a causal interpretation. Subjects include heavy emphasis on data-generating processes and causal diagrams. Concepts are demonstrated with a heavy emphasis on graphical intuition and the question of what we do to data. When we "add a control variable" what does that actually do?"--
"A Chapman & Hall book."
Includes bibliographical references (pages [601]-615) and index.
Keywords: Causality (Physics); Design -- Research